New Textbooks for Teaching Philosophy of Science. - Pâslaru, Viorel (Philosophy of Science, 2023)
It develops three types of criticism of science, usually lumped together: the prevalent image of science, the flaws in the practice of science, and the institution of science that threatens significant goals and values. That work considered instead the diversity of the sciences and questioned the ideal of a unified science committed to reductionism in favor of analyzing the practices of various sciences along the lines of Cartwright's vision of a "dappled world." Chapter 6 examines first the traditional aims of science and shows that what is explained, predicted, and controlled, or what truths are investigated is not neutral, but is determined by people doing science, or those financing it, and how their value preferences determine the aims of science. Science comes in a variety of scientific activities and there is no special list of features that guarantees good science; however, generalizations can be made about how good science is done.